The HUBUNGAN KONDISI FISIK RUMAH DAN PERILAKU DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS SOSIAL TAHUN 2024 - Anwar, Khairil Anwar; Dwi Maharani, Nabila; Maksuk, Maksuk (Poltekkes Kemenkes Bengkulu, 2024)
Dengue Hemorrhagic Fever (DHF) is a type of disease caused by the dengue virus, and its spread is made easier by an intermediary vector, namely the Aedes aegypti mosquito. There are several factors that can influence the distribution and increase in dengue cases in an area, including human factors (host), vector (mosquito), dengue virus (agent) and environmental factors (environment). The aim of this research is to determine the relationship between the physical condition of the house and behavior with the incidence of Dengue Hemorrhagic Fever (DHF) in the Working Area of ​​the Social Health Center, Sukarami District, Palembang City in 2024. This research is an analytical survey with a case control approach. This study used a case and control ratio of 1:2, with a total of 27 cases and 54 controls, so the total sample in this study was 81 samples. The case and control sampling technique is purposive sampling. Data were analyzed using the chi-square test. The results of this study show that there is no relationship between the physical condition of the house and the p-value (p=0.542), there is no relationship between knowledge and the p-value (p=1.000), there is a relationship between attitudes and the p-value (p=0.007), there is a relationship action with a p-value (p=0.022), there is a relationship between the presence of larvae with a p-value (p=0.045) with the incidence of dengue fever in the Sukarami District Social Health Center Working Area. The conclusion of this research is that there is a significant relationship between attitudes, actions and the presence of larvae, while there is no significant relationship between the physical condition of the house and knowledge and the incidence of dengue fever in the Sukarami District Social Health Center Work Area. To the community health center officers and the community, to further increase dengue prevention activities systematically in order to reduce the number of dengue fever incidents in the work area of ​​the Social Health Center.